Estimating the velocity of pyroclastic density currents using an operational dual-PRF radar - Magfira Syarifuddin (2022)
Pyroclastic density currents are one of the deadliest hazards produced by a volcano. Understanding their dynamics and generation mechanisms is critical for developing better hazard mitigation strategies. This study presents a method for retrieving velocity profiles across a natural moving PDC, applied here to a PDC generated by collapsing column during the eruption of Sinabung Volcano, Indonesia, on 19 February 2018 at the onset time of 08:53. We used an operational dual Pulse Repetition Frequency (PRF) weather radar, located ~7.8 km to the SE of the volcano, to estimate the velocity profile components of the volcanic plume: updraft, fallout, and horizontal advection. Doppler radar data was post-processed by applying two different filters: median and Laplacian, to correct errors associated with dealiased Doppler velocities. The Laplacian filter method was more effective in correcting the dealiasing errors by producing a more continuous velocity field without over smoothing its values. Following the dealiasing process, the velocity profile components were retrieved according to radar parameters such as Doppler velocities, copolar correlation, and reflectivity intensity factor. Initially, the pyroclastic clast was released at a lower exit velocity of ~120 m/s (84 s after the onset). A maximum of ~190 m/s exit velocity was then observed at 08:57:52 (292 s after onset). Lower exit velocity in the initial phase and less than 10 m/s estimated wind speed are the main factors causing the partial collapse of the plume at ~2.5 km height above the vent. The part of the collapsing column was associated with a more than 50 dBZ reflectivity intensity factor of fallout velocity exceeding −50 m/s at 126 s after the onset. Dilute PDCs were observed until 09:09:34 (994 s after onset), moving downslope at SE sector at a maximum velocity of −84 m/s (i.e., in the direction of the radar). The extracted velocity components are essential parameters in the numerical model of PDCs and tephra dispersal, enforcing the benefit of weather radar to complement the remote monitoring system of volcanic hazards.